Assessment of Dysmenorrhea Symptoms Using the Cox Retrospective Symptom Scale and Knowledge of Traditional Medicine in the Management of Dysmenorrhea among Women Aged Over 18 and of Reproductive Age - Hung, Nguyen Van; Buoi, Bui Thi; Ky Duyen, Nguyen Cao; Ngoc, Tran Thi Nhu; Phuoc, Le Thanh; Kien Quoc, Le Ba; Son, Luong Giang (VNU Journal of Science: Medical and Pharmaceutical Sciences, 2026)
Objective: This study aimed to assess dysmenorrhea symptoms using the RSS-Cox scale and to evaluate knowledge regarding traditional medicine methods for supporting the management of dysmenorrhea among women over 18 years old and within reproductive age in Kim Long Ward, Hue City. Results: The prevalence of dysmenorrhea among women in Kim Long Ward was 86.5%. Pain levels assessed by the VAS scale showed 56.7% with mild pain, 22.8% with moderate pain, and 7.0% with severe pain. The mean RSS – Cox 1 score was 16.8 ± 9.5, and the mean RSS – Cox 2 score was 17.2 ± 9.9. Additionally, 73.1% of participants had knowledge of traditional medicine–based supportive methods for dysmenorrhea, with warm compression being the most commonly used practice. Conclusion: Dysmenorrhea is a highly prevalent condition among women over 18 years old and within reproductive age. Although most cases present with mild pain, menstrual-related symptoms occur frequently and with notable severity. Awareness of traditional medicine methods for supporting dysmenorrhea management is relatively high in this population.